Timber disease in forest plantation / Zaida Suod, Norfazuinda Mohd Fuzai and Nurzawani Lazim - Suod, Zaida; Mohd Fuzai, Norfazuinda; Lazim, Nurzawani (2006)
Forestry in Peninsular Malaysia consists from many type of forestry. One of it is forest plantation which is a man-made forest. This means, it is unnatural forest. Forest Plantation is established to maintain self-sufficiency of forest resource and timber supply in peninsular Malaysia, because of the shortage of the natural forest. From the history of plantation which began in 1887 until now, it showed that forest plantation is always built on with back-up from research and studies. Otherwise, the choice of a good species is important. And it is base on specifics criteria. Besides that we must take seriously about the management aspects of the species. Now days, the forest plantation management have pay less attention to the problem of disease study. The treatment operation is done in order to encourage healthy growth of young trees.